PENGARUH BEBERAPA VARIETAS DAN MEDIA TANAM HIDROPONIK SISTEM SUBSTRAT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNCIS (Phaseolus vulgaris L.) - Atik Ayu Wariska; Kacung Hariyono (Berkala Ilmiah Pertanian, 2020)
Beans (Phaseolus vulgaris L.) is a type of nut plant originating from America which is widely used as a vegetable and harvested at a younger age, which can be planted at an altitude of approximately 300 masl to above 1000 masl (Rukmana, 1994). The reduction of agricultural land in the city can be one of the problems in the cultivation of home-scale beans, where it is necessary to act on a cultivation system that can be used on a narrow land but the result of productivities are able to meet daily needs. One of them is by using a substrate hydroponic system which is still rarely used for beans since there is no knowledge of farmers about the suitable media types used in the substrate hydroponic system. Other effort that can be made to meet the needs of beans in urban areas is by using superior varieties. One type of beans that is widely cultivated by farmers is the creeping beans, where it can be harvested with a longer period. The purpose of this research is to find out varieties of creeping beans which are able to grow well on the hydroponic media substrate system. By knowing the type of hydroponic media that is good for several varieties of beans, is expected to increase the growth and yield of beans on a land scale that is less extensive or less productive. The experimental design used in this study was a factorial completely randomized design with 3 replications. The data obtained would be analyzed using analysis of variance (ANOVA). If there is significantly different between treatments, the real difference test will be performed with Duncan’s multiple range of 5%. The results showed a combination of treatments between varieties and substrate hydroponic media in the form of cocopeat, husk charcoal and sawdust can affect the number of crop pods, crop pod weight, stover wet weight and stover dry weight. The treatment of using several bean varieties can affect the length of crop pods and the width of crop pods. The use of hydroponic substrate media type is able to affect the height of bean plants. Keywords: Beans, Varieties, Substrat Hydroponic Media